Exosomes in osteoarthritis: Updated insights on pathogenesis, diagnosis, and treatment - Fan, Wen-Jin; Liu, Di; Pan, Lin-Yuan; Wang, Wei-Yang; Ding, Yi-Lan; Zhang, Yue-Yao; Ye, Rui-Xi; Zhou, Yang; An, Sen-Bo; Xiao, Wen-Feng (Frontiers in Cell and Developmental Biology, 2022)
Osteoarthritis (OA) has remained a prevalent public health problem worldwide over the past decades. OA is a global challenge because its specific pathogenesis is unclear, and no effective disease-modifying drugs are currently available. Exosomes are small and single-membrane vesicles secreted via the formation of endocytic vesicles and multivesicular bodies (MVBs), which are eventually released when MVBs fuse with the plasma membrane. Exosomes contain various integral surface proteins derived from cells, intercellular proteins, DNAs, RNAs, amino acids, and metabolites. By transferring complex constituents and promoting macrophages to generate chemokines and proinflammatory cytokines, exosomes function in pathophysiological processes in OA, including local inflammation, cartilage calcification and degradation of osteoarthritic joints. Exosomes are also detected in synovial fluid and plasma, and their levels continuously change with OA progression. Thus, exosomes, specifically exosomal miRNAs and lncRNAs, potentially represent multicomponent diagnostic biomarkers for OA. Exosomes derived from various types of mesenchymal stem cells and other cell or tissue types affect angiogenesis, inflammation, and bone remodeling. These exosomes exhibit promising capabilities to restore OA cartilage, attenuate inflammation, and balance cartilage matrix formation and degradation, thus demonstrating therapeutic potential in OA. In combination with biocompatible and highly adhesive materials, such as hydrogels and cryogels, exosomes may facilitate cartilage tissue engineering therapies for OA. Based on numerous recent studies, we summarized the latent mechanisms and clinical value of exosomes in OA in this review.